2014
DOI: 10.1002/acn3.157
|View full text |Cite
|
Sign up to set email alerts
|

Visual pathway neurodegeneration winged by mitochondrial dysfunction

Abstract: ObjectivesTo test for structural and functional contribution of mitochondrial dysfunction to neurodegeneration in multiple sclerosis (MS). A visual pathway model void of MS lesions was chosen in order to exclude neurodegeneration secondary to lesion related axonotmesis.MethodsA single-centre cohort study (230 MS patients, 63 controls). Spectral domain optical coherence tomography of the retina, 3T magnetic resonance imaging of the brain, spectrophotometric assessment of serum lactate levels. Postmortem immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…Simons et al suggest that the greater variability of degeneration in the CNS depends on the stoichiometry of the axon-oligodendrocyte relationship which varies in different parts of the brain. There is prospective data to suggest that such a relationship can be tested in vivo by combining body fluid biomarkers with MRI and retinal OCT (Petzold et al 2015). Particularly neurofilament proteins, specific biomarkers for neurodegeneration, have advanced the field (Khalil et al 2018;Petzold 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Simons et al suggest that the greater variability of degeneration in the CNS depends on the stoichiometry of the axon-oligodendrocyte relationship which varies in different parts of the brain. There is prospective data to suggest that such a relationship can be tested in vivo by combining body fluid biomarkers with MRI and retinal OCT (Petzold et al 2015). Particularly neurofilament proteins, specific biomarkers for neurodegeneration, have advanced the field (Khalil et al 2018;Petzold 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, imaging studies in MS patients indicate that both glucose and lactate metabolism is increased in active MS lesions [ 39 , 41 , 50 ]. Lactate levels were also found to be increased in the CSF and serum of MS patients and to correlate with disease progression [ 1 , 35 ]. These studies suggest that the changes in GME expression levels we found are associated with alterations in the glycolytic and TCA cycle fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal healthy state, the generation of ROS occurs in a controlled manner, with mitochondria as the main intracellular source of ROS in the form of superoxide anions through the electron transport chain [2]. Increased ROS production occurs under high-stress conditions or in various disease states such as acute [3,4] and chronic neurodegenerations [5], stroke [6], ischemia [7] and male infertility [8]. These pathologic conditions are characterized by malfunctioning mitochondria, which are unable to correctly catalyze the tetravalent reduction of molecular oxygen to water in the electron transport chain, leading to increased ROS generation from aerobic respiration.…”
Section: Introductionmentioning
confidence: 99%